2016
DOI: 10.1007/s00170-016-8494-7
|View full text |Cite
|
Sign up to set email alerts
|

Image processing as a tool for high-pressure water jet coating removal assessment

Abstract: The paper reports about investigations into the removal of thick organic protective coatings with rotating highspeed water jets. Ten nozzle carriers, rotating at a very high speed of 3000 min 1 , were applied at stand-off distances between 10 and 82 mm. Widths of the eroded sections and the percentage of completely exposed steel sections were estimated. Color-based image processing was applied for the assessment of exposed steel sections. The results reveal two types of performance. (i) Carriers with a moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…High-pressure water jetting processes are being used more and more [31]. The possible applications include cleaning processes, decoating processes, cutting processes and others [32].…”
Section: Types and Sources Of Datamentioning
confidence: 99%
“…High-pressure water jetting processes are being used more and more [31]. The possible applications include cleaning processes, decoating processes, cutting processes and others [32].…”
Section: Types and Sources Of Datamentioning
confidence: 99%
“…Chomka and Chudy [ 23 ] took a mathematical analysis of the cleaning trajectory distribution of double-nozzle rotary nozzles, and confirmed the range of the optimal moving speed and angular velocity to make the cleaning trajectory evenly distributed. Momber [ 24 ] used image processing method to evaluate the influence of parameters such as micro channel diameter of nozzle, number of nozzles, inject angle, target distance, and flow rate on paint removal effect, and optimized the jet paint removal parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [18] studied the variation law of waterjet cutting pressure and the mechanism of permeability enhancement, and they determined the rectification cutting effect of the cutting nozzle. Momber [19] studied the relationship between the number of nozzles and the shock effect and found that the most effective configuration is characterized by an optimum balance between nozzle number, nozzle diameter, and nozzle orbit for a given stand-off distance.…”
Section: Introductionmentioning
confidence: 99%